Festlegung von Flugrouten (Flughafen Frankfurt a. M.). BVerwG, Urteil vom 24.6.2004 - 4 C 11/03. - (:unkn) unknown (Heymann, 2004)
§§ 9, 29, 29 b LuftVG; §§ 6, 27 a, 36 LuftVO; § 3 BImSchG. difu
Keywords: Verkehr; Luftverkehr; Flughafen; Gemeinde; Umweltschutz; Lärmbelastung; Fluglärm; Luftverkehrsrecht; Festlegung; Flugroute; Zumutbarkeit; Fluglärmschutz